Analisis Pengelolaan Anggaran Belanja di Australian Islamic College of Sydney dalam Perspektif Manajemen Pembiayaan Pendidikan - Kusyairi, Mochamad Irsyad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze the management of expenditure budgeting at the Australian Islamic College of Sydney (AICS) from the perspective of educational finance management. The research employs a qualitative-descriptive approach, relying on the 2023 Annual Report of AICS as the primary data source. Findings indicate that 67% of the institution’s total expenditures are allocated for staff salaries and related benefits. This dominant proportion limits the flexibility of the institution in financing other essential aspects such as curriculum development, facility upgrades, and pedagogical innovation. Through a literature-based analysis, this study compares the current budgeting practice of AICS with ideal educational finance models that emphasize balanced allocation, cost-effectiveness, and long-term educational outcomes. The research concludes that the overconcentration of funds on salary expenditure presents challenges to sustainable quality improvement and recommends a strategic reallocation based on performance-based budgeting and efficiency principles. This study contributes by providing an academic perspective on budget management in Islamic schools abroad, which has received limited scholarly attention, and offers practical insights for achieving financial efficiency in similar institutions.